Enhancing reading interest among down syndrome children through a reading aloud programme - Shafie, Hidayu; Samsudin, Sri Rahayu; Turiman, Syamimi; Mohaini, Muhammad Luthfi (Universiti Teknologi MARA, Kedah, 2024)
Individuals with Down syndrome commonly face challenges in developing literacy skills. Previous studies supported the view that being read to from an early age can assist children with Down syndrome develop their spoken language and memory skills. Hence, early intervention programs that are structured and interactive are needed to foster a positive attitude towards reading. This study explores the impact of a reading aloud programme to enhance reading interest among children with Down syndrome. The reading aloud programme involved Down syndrome children at ORKIDS (Persatuan Kebajikan Anak-anak Istimewa Selangor), a learning centre that supports children with Down syndrome. The programme was implemented over a period of three months where the children were read to by trained volunteers who are lecturers and students at Akademi Pengajian Bahasa, Universiti Teknologi MARA. Eight sessions were conducted using carefully selected story books. Two ORKIDS teachers were interviewed to gather feedback related to the children’s reading interests. Findings indicate that the reading aloud sessions improved the children’s interest in reading. Through the interviews conducted, the teachers observed increased interest in reading activities, and increased frequency of voluntary reading activities at ORKIDS. This study highlights the potential of reading aloud programmes which function as an effective intervention to enhance literacy interest and skills among children with Down syndrome. The findings suggest that such a programme can be a valuable addition to the special education syllabus for literacy development. Further research is recommended to explore long-ter effects and the applicability of such activities across diverse educational settings.